Statistical Methods of the Supply Chain Standards to Evaluate the Shadow Economy in the Republic of Sakha - A. Karatayeva, Tamara; V. Danilova, Elena; T. Parfenova, Olga; V. Evseev, Prokopiy; E. Kampeeva, Elena (International Journal of Supply Chain Management, 2020)
Hiding of economic relations is one of the most significant obstacles to ensuring sustainable economic development, improving the welfare and standard of living of the population and strengthening national security. The purpose of the research is to conduct a comparative analysis of external factors of innovative development of supply chain management and its transparency, which is the main factor in the transition to a new level of economic relations and reducing shadow economy. This article presents a comprehensive study of the parameters of a shadow economy, considers its essence, and defines its terminology. The study examined the specifics of the statistical methods applied in assessing various structural elements of a shadow economy and measured and assessed the shadow economy in supply chain strategies in this region. The research conducted enabled the authors to formulate the main measures required to reduce the shadow economy by applying the supply chain management.